Process for preparing a polybutadiene latex and process for preparing polybutadiene rubber

CN116987218BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210442793.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-25
Publication Date
2026-10-13
Estimated Expiration
2042-04-25

AI Technical Summary

Technical Problem

[0004]至今,镍系顺丁橡胶(NiBR)生产技术已经工业化已有40多年,各方面均取得了很大进步,但产品牌号单一

Benefits of technology

[0039]另外,本发明的方法,可以使用现有装置而无需增加设备改造费用,从而能够显著降低成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of butadiene polymerization, and discloses a preparation method of polybutadiene glue solution and a preparation method of polybutadiene rubber.The preparation method of the glue solution comprises the following steps: 1) mixing component N and a first component B, and then aging to obtain a mixed component; 2) mixing component A, a second component B and a first butadiene, then mixing the second mixed product with a first component C, and then aging to obtain a second mixed component; 3) polymerizing a second butadiene, the mixed component and a second component C, and then adding a third component B and the second mixed component to carry out polymerization when the polymerization conversion rate is more than 70%; wherein the component N is a nickel salt; the component B is an alkyl aluminum compound; the component C is a halogenated compound; and the component A is a rare earth salt.According to the present application, the polybutadiene rubber has the advantages of good wear resistance, easy processing, simple process, simple operation, mild conditions and suitability for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of butadiene polymerization, and more specifically, to a method for preparing polybutadiene adhesive and a method for preparing polybutadiene rubber. Background Technology

[0002] Polybutadiene rubber (PPB) possesses high elasticity, excellent abrasion resistance, and good heat resistance, aging resistance, flexural strength, low heat generation, and low hysteresis loss. Furthermore, its raw material resources are abundant and inexpensive, making it particularly suitable for tire manufacturing. Since a US company pioneered the industrial production of PPB using titanium-based catalysts and solution polymerization in 1960, production has rapidly expanded with the development of the petrochemical industry and driven by the tire manufacturing sector. By 1964, its production capacity ranked second among the seven major general-purpose synthetic rubbers, second only to styrene-butadiene rubber (SBR). Currently, many countries and regions worldwide have industrial production facilities for PPB.

[0003] In 1958, Takeshi Matsumoto and others first discovered that reduced nickel supported on acidic substances had the ability to initiate butadiene polymerization. This marked the beginning of nickel-based directed polymerization of butadiene. Around 1965, Japan and other countries were the first to industrialize butadiene polymerization using a ternary nickel system consisting of nickel naphthenate, triethylaluminum, and boron trifluoride diethyl ether complex, with toluene as a solvent. In the early 1970s, my country also industrialized nickel-based cis-butadiene rubber using hydrogenated gasoline as a solvent and a ternary nickel system consisting of nickel naphthenate, triisobutylaluminum, and boron trifluoride diethyl ether complex, employing a nickel-aluminum aging process followed by the addition of dilute boron.

[0004] Nickel-based butadiene rubber (NiBR) production technology has been industrialized for over 40 years, achieving significant progress in various aspects, but the product range remains limited. Faced with the implementation of tire labeling regulations and the ever-increasing demands on materials from societal development, the nickel-based butadiene process can no longer meet the requirements for easy processing and wear resistance. Therefore, a method for preparing easily processable and wear-resistant polybutadiene rubber is needed. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing polybutadiene adhesive and a method for preparing polybutadiene rubber. The polybutadiene rubber prepared by this method is easy to process and has good wear resistance. It also has the advantages of simple process, easy operation and mild conditions, and is suitable for large-scale industrial production.

[0006] To achieve the above objectives, the first aspect of the present invention provides a method for preparing polybutadiene adhesive, characterized in that the method includes the following steps:

[0007] 1) After mixing component N and the first component B, the mixture is aged to obtain the first mixed component;

[0008] 2) After mixing component A, second component B and first butadiene in a second mixture, the product of the second mixture is subjected to a second aging process with first component C to obtain a second mixed component;

[0009] 3) The second butadiene, the first mixed component, and the second component C are subjected to a first polymerization reaction. When the polymerization conversion rate is above 70%, the third component B and the second mixed component are added to carry out a second polymerization reaction.

[0010] In this composition, component N is a nickel salt; component B is an alkylaluminum compound; component C is a halogenated compound; and component A is a rare earth salt.

[0011] In step 2), the molar ratio of component A, the second component B, the first butadiene, and the first component C is 1:8-20:10-80:2-5.

[0012] Preferably, in step 1), the molar ratio of component N to the first component B is 1:2-12.

[0013] Preferably, based on the component N1 mmol contained in the first mixed component, in step 2), the amount of component A is 0.01-1 mmol, the amount of the second component B is 0.12-20 mmol, the amount of the first butadiene is 2-60 mmol, and the amount of the first component C is 0.2-3.5 mmol.

[0014] Preferably, in step 2), the molar ratio of component A, the second component B, the first butadiene, and the first component C is 1:9-15:40-50:3-4.

[0015] Preferably, based on the component N1 mmol contained in the first mixed component, in step 3), the amount of the second component C is 0.01-1 mmol.

[0016] Preferably, in step 3), the molar ratio of the second butadiene, the first mixed component based on component N, the second component C, the third component B, and the second mixed component based on component A is 1:5×10. -5 -1.2×10 -4 1×10 -5 -4×10 -5 2×10 -5 -4×10 -4 5×10 -6 -3×10 -5 .

[0017] Preferably, the alkylaluminum compound is selected from at least one of trialkylaluminum and dialkylaluminum hydride.

[0018] Preferably, the trialkylaluminum is represented by the formula Al(R)3, and the dialkylaluminum hydride is represented by the formula AlH(R)2, wherein each R in the formula Al(R)3 and AlH(R)2 is independently selected from C1-C6 alkyl groups.

[0019] More preferably, the alkylaluminum compound is at least one selected from trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, tri-n-pentylaluminum, tri-n-hexylaluminum, triisobutylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, and diisobutylaluminum hydride.

[0020] Preferably, the halogenated compound is selected from at least one of boron halo, hydrogen halo, alkylaluminum halo, silane and sesquihaloalkylaluminum.

[0021] Preferably, the haloalkylaluminum is of the formula Al(R) 1 )2X indicates that the halosilane is derived from the formula Si(R 1 ) 4-n X n This indicates that the sesquihaloalkylaluminum is made of the formula Al2(R 1 )3X3 means that, in the formula Al(R) 1 )2X, formula Si(R) 1 ) 4-n X n The sum of Al2(R) 1 Each R in 3x3 1 Each of the X groups is independently selected from C1-C6 alkyl, benzyl, and allyl groups, and each X group is independently selected from halogens, with n being an integer from 1 to 4.

[0022] Preferably, the halogenated compound is at least one selected from diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, sesquiisobutylaluminum chloride, monochlorosilane, dichlorosilane, trichlorosilane, silicon tetrachloride, hydrogen fluoride, and boron trifluoride diethyl ether complex.

[0023] Preferably, the conditions for the first mixing include: a temperature of 10-40°C and a time of 10-200 min.

[0024] Preferably, the conditions for the first aging process include: a temperature of 10-80°C and a time of 10-90 minutes.

[0025] Preferably, the conditions for the second mixing include: a temperature of 10-80°C and a time of 10-200 min.

[0026] Preferably, the conditions for the second aging process include: a temperature of 30-80°C and a time of 30-300 min.

[0027] Preferably, the temperature of the first polymerization reaction is 40-90°C.

[0028] Preferably, the temperature of the second polymerization reaction is 40-90°C.

[0029] Preferably, the total reaction time of the first polymerization reaction and the second polymerization reaction is 1-36 hours, more preferably 6-7 hours.

[0030] Preferably, steps 1) through 3) are each carried out independently in an inert atmosphere.

[0031] Preferably, the inert atmosphere is provided by at least one of nitrogen, helium, and argon.

[0032] Preferably, the first mixed component and the second mixed component each contain a solvent independently, or the raw materials for the first polymerization reaction contain a solvent.

[0033] Preferably, the solvent is at least one of C5-C10 alkanes, C5-C10 cycloalkanes, and C6-C12 aromatics.

[0034] Preferably, the solvent is at least one selected from pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene, and cumene.

[0035] According to a second aspect of the present invention, a method for preparing polybutadiene rubber is provided, wherein the method includes the following steps:

[0036] 1) The step of preparing polybutadiene adhesive by the method for preparing polybutadiene adhesive according to the first aspect of the present invention;

[0037] 2) The step of preparing polybutadiene rubber from the polybutadiene solution.

[0038] The above technical solutions can improve the wear resistance of polybutadiene rubber and make it easier to process. They also have the advantages of simple process, easy operation and mild conditions, making them suitable for large-scale industrial production.

[0039] In addition, the method of the present invention can use existing equipment without increasing equipment modification costs, thereby significantly reducing costs. Detailed Implementation

[0040] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0041] This invention provides a method for preparing polybutadiene adhesive, characterized in that the method includes the following steps:

[0042] 1) After mixing component N and the first component B, the mixture is aged to obtain the first mixed component;

[0043] 2) After mixing component A, second component B and first butadiene in a second mixture, the product of the second mixture is subjected to a second aging process with first component C to obtain a second mixed component;

[0044] 3) The second butadiene, the first mixed component, and the second component C are subjected to a first polymerization reaction. When the polymerization conversion rate is above 70%, the third component B and the second mixed component are added to carry out a second polymerization reaction.

[0045] Among them, component N is a nickel salt; component B is an alkyl aluminum compound; component C is a halogenated compound; and component A is a rare earth salt.

[0046] In this invention, the first component B, the second component B, and the third component B may be the same or different. Similarly, the first component C and the second component C may be the same or different.

[0047] The present invention will be described step by step below. However, it should be noted that the order of steps 1) and 2) of the present invention is not limited. Step 1) can be performed first and then step 2), or step 2) can be performed first and then step 1), or steps 1) and 2) can be performed simultaneously.

[0048] Step 1): Mix component N and first component B in the first stage and then age them in the first stage to obtain the first mixed component.

[0049] According to the present invention, in order to obtain polybutadiene rubber that is easy to process and has excellent wear resistance, preferably, in step 1), the molar ratio of component N to first component B is 1:2-12, more preferably 1:3-8, even more preferably 1:5-6.5, and even more preferably 1:5-6.1.

[0050] According to the present invention, in order to obtain polybutadiene rubber that is easy to process and has excellent wear resistance, preferably, the conditions for the first mixing include: a temperature of 10-40°C and a time of 10-200 min; more preferably, the conditions for the first mixing include: a temperature of 10-40°C and a time of 20-60 min.

[0051] According to the present invention, in order to obtain polybutadiene rubber that is easy to process and has excellent wear resistance, preferably, the first aging conditions include: a temperature of 10-80°C and a time of 10-90 min; more preferably, the first aging conditions include: a temperature of 15-35°C and a time of 15-50 min.

[0052] According to the present invention, component N is a nickel salt. The nickel salt can be any of the various nickel salts commonly used in the art for butadiene polymerization. Preferably, the nickel salt is one or more of nickel naphthenate, nickel octanoate, and nickel benzoate.

[0053] The nickel salts described above can be obtained using conventional methods in the art, such as commercially available products or prepared using conventional methods in the art, and the present invention does not particularly limit them in this regard.

[0054] Step 2): After mixing component A, second component B, and first butadiene in a second mixture, the product of the second mixture is... The mixture is subjected to a second aging process with the first component C to obtain a second mixed component.

[0055] According to the present invention, in order to obtain polybutadiene rubber that is easy to process and has excellent wear resistance, based on the component N1 mmol contained in the first mixed component, in step 2), the amount of component A is 0.01-1 mmol, the amount of the second component B is 0.12-20 mmol, the amount of the first butadiene is 2-60 mmol, and the amount of the first component C is 0.2-3.5 mmol; preferably, based on the component N1 mmol contained in the first mixed component, in step 2), the amount of component A is 0.1-0.5 mmol, the amount of the second component B is 1-10 mmol, the amount of the first butadiene is 1-30 mmol, and the amount of the first component C is 0.22-2 mmol.

[0056] Furthermore, in order to further improve the wear resistance of the obtained polybutadiene rubber, preferably, in step 2), the molar ratio of component A, the second component B, the first butadiene, and the first component C is 1:8-20:10-80:2-5; more preferably, in step 2), the molar ratio of component A, the second component B, the first butadiene, and the first component C is 1:8-18:30-55:2.8-4; even more preferably, in step 2), the molar ratio of component A, the second component B, the first butadiene, and the first component C is 1:9-15:40-50:3-4.

[0057] According to the present invention, in order to obtain polybutadiene rubber that is easy to process and has excellent wear resistance, preferably, the second mixing conditions include: a temperature of 10-40°C and a time of 10-200 min; more preferably, the second mixing conditions include: a temperature of 10-40°C and a time of 20-60 min.

[0058] According to the present invention, in order to obtain polybutadiene rubber that is easy to process and has excellent wear resistance, preferably, the conditions for the second aging include: a temperature of 30-80°C and a time of 30-300 min; more preferably, the conditions for the second aging include: a temperature of 50-70°C and a time of 60-120 min.

[0059] According to the present invention, component A is a rare earth salt. The rare earth salt can be any of the various rare earth salts commonly used in the art for butadiene polymerization. Preferably, the rare earth salt is one or more of neodymium salts, cerium salts, and praseodymium salts. Examples of such rare earth salts include neodymium octanoate, neodymium naphthenate, and neodymium phosphonate.

[0060] The above-mentioned rare earth salts can be obtained in a manner conventional in the art, such as commercially available products, or prepared using methods conventional in the art, and the present invention does not have any particular limitation in this regard.

[0061] According to the present invention, component B is an alkylaluminum compound. The alkylaluminum compound can be any of the various alkylaluminum compounds commonly used in the art for butadiene polymerization. To further improve the abrasion resistance of the obtained polybutadiene rubber, preferably, the alkylaluminum compound is selected from at least one of trialkylaluminum and dialkylaluminum hydride; more preferably, the trialkylaluminum is represented by the formula Al(R)3, and the dialkylaluminum hydride is represented by the formula AlH(R)2, wherein each R in formula Al(R)3 and formula AlH(R)2 is independently selected from C1-C6 alkyl groups; even more preferably, the alkylaluminum compound is at least one of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, tri-n-pentylaluminum, tri-n-hexylaluminum, triisobutylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, and diisobutylaluminum hydride.

[0062] According to the present invention, component C is a halogenated compound. The halogenated compound can be any of the various halogenated compounds commonly used in the art for butadiene polymerization. To further improve the abrasion resistance of the obtained polybutadiene rubber, preferably, the halogenated compound is selected from at least one of boron halo, hydrogen halo, alkylaluminum halo, silane halo, and sesquihaloalkylaluminum; more preferably, the alkylaluminum halo is of the formula Al(R 1 )2X indicates that halosilanes are derived from the formula Si(R 1 ) 4-n X n It indicates that sesquihaloalkylaluminum is produced by the formula Al2(R 1 )3X3 means that, in the formula Al(R) 1 )2X, formula Si(R) 1 ) 4-n X n The sum of Al2(R) 1 Each R in 3x31 Each of the alkyl, benzyl, and allyl groups independently selected from C1-C6, each X independently selected from halogens, and n being an integer from 1 to 4; more preferably, the halogenated compound is at least one selected from diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, sesquiisobutylaluminum chloride, monochlorosilane, dichlorosilane, trichlorosilane, silicon tetrachloride, hydrogen fluoride, and boron trifluoride diethyl ether complex.

[0063] Step 3): The second butadiene, the first mixed component, and the second component C undergo a first polymerization reaction, during which the polymerization conversion... When the polymerization rate is above 70%, the third component B and the second mixed component are added to carry out the second polymerization reaction.

[0064] According to the present invention, in order to further improve the wear resistance of the obtained polybutadiene rubber, preferably, based on the component N1 mmol contained in the first mixed component, the amount of the second component C in step 3) is 0.01-1 mmol; more preferably, based on the component N1 mmol contained in the first mixed component, the amount of the second component C in step 3) is 0.1-1 mmol.

[0065] According to the present invention, in order to further improve the abrasion resistance of the obtained polybutadiene rubber, preferably, in step 3), the molar ratio of the second butadiene, the first mixed component based on component N, the second component C, the third component B, and the second mixed component based on component A is 1:5×10. -5 -1.2×10 -4 1×10 -5 -4×10 -5 2×10 -5 -4×10 -4 5×10 -6 -3×10 -5 More preferably, in step 3), the molar ratio of the second butadiene, the first mixed component based on component N, the second component C, the third component B, and the second mixed component based on component A is 1:8×10. -5 -1×10 -4 2.5×10 -5 -3.5×10 -5 5×10 -5 -1.5×10 -4 8×10 -6 -2.5×10 -5 .

[0066] According to the present invention, in order to further improve the wear resistance of the obtained polybutadiene rubber, preferably, a third component B and a second mixed component are added to carry out a second polymerization reaction when the polymerization conversion rate is 70-95%; more preferably, a third component B and a second mixed component are added to carry out a second polymerization reaction when the polymerization conversion rate is 75-90%.

[0067] According to the present invention, in order to further improve the wear resistance of the obtained polybutadiene rubber, preferably, the first polymerization reaction and the second polymerization reaction each independently satisfy at least the following conditions: the temperature is 40-90°C, preferably 45-55°C.

[0068] In this invention, preferably, the total reaction time of the first polymerization reaction and the second polymerization reaction is 1-36 hours, more preferably 6-7 hours.

[0069] Furthermore, in order to prevent oxygen from damaging the active sites of the catalyst, steps 1)-3) are preferably carried out independently in an inert atmosphere; more preferably, the inert atmosphere is provided by at least one of nitrogen, helium and argon.

[0070] Meanwhile, in order to enable the catalyst to successfully construct its active center and achieve higher catalytic activity, preferably, the first mixed component and the second mixed component each contain a solvent independently, or the raw materials for the first polymerization reaction contain a solvent; more preferably, the solvent is at least one of C5-C10 alkanes, C5-C10 cycloalkanes and C6-C12 aromatics; even more preferably, the solvent is at least one of pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene and cumene.

[0071] In the above embodiments, in order to further improve the activity of the catalyst, preferably, the concentration of component N in the first mixed component and the second mixed component is 0.01-1 mmol / mL, more preferably 0.05-0.2 mmol / mL, and more preferably 0.08-0.12 mmol / mL.

[0072] In the above embodiments, the solvent can be added in the form of a pure substance or in the form of a solution with other reactants.

[0073] Based on this, component N can be provided in the form of a pure substance or in the form of a solution. When component N is provided in the form of a solution, the concentration of the solution of component N can be, for example, 0.01-0.5 mol / L. The solvent can be selected from the solvents described above.

[0074] Similarly, component B can be provided either as a pure substance or as a solution. When component B is provided as a solution, the concentration of the solution can be, for example, 0.01-5 mol / L. The solvent can be selected from the solvents described above.

[0075] Similarly, component C can be provided either as a pure substance or as a solution. When component C is provided as a solution, the concentration of the solution can be, for example, 0.0001-5 mol / L. The solvent can be selected from the solvents described above.

[0076] Similarly, component A can be provided either as a pure substance or as a solution. When component A is provided as a solution, the concentration of the solution can be, for example, 0.01-0.5 mol / L. The solvent can be selected from the solvents described above.

[0077] Furthermore, butadiene can be provided either as a pure substance or in solution form. When butadiene is provided in solution form, the weight ratio of butadiene to solvent is 100:300-1000. The solvent can be C5-C... 10 Alkanes, C5-C 10 Cycloalkanes and C6-C 12 At least one of the aromatic hydrocarbons; more preferably, the solvent is at least one of pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene and cumene.

[0078] According to another aspect of the present invention, a method for preparing nickel-based cis-butadiene rubber is provided, wherein the method includes the following steps:

[0079] 1) The step of preparing polybutadiene adhesive by the method for preparing polybutadiene adhesive according to the first aspect of the present invention;

[0080] 2) The step of preparing polybutadiene rubber from the polybutadiene solution.

[0081] According to the present invention, there is no particular limitation on the "step of preparing polybutadiene rubber from the polybutadiene solution". Conditions and methods commonly used in the art can be adopted. For example, after the reaction is completed, anhydrous ethanol and antioxidant 1076 can be added to the solution to terminate the reaction, and then coagulation can be carried out. The obtained butadiene polymer is dried at room temperature and then placed in a vacuum drying oven at 50°C until constant weight.

[0082] The present invention will be described in detail below through examples, but the present invention is not limited to the following embodiments.

[0083] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available.

[0084] The conversion rate of the polymer monomer is calculated using the following formula.

[0085]

[0086] The method for determining the "content of cis-1,4-polymer structure" is as follows:

[0087] The microstructure of the polymer was determined using conventional Fourier transform infrared spectroscopy (FTIR). Polybutadiene rubber was prepared as a 5 wt% hexane solution, coated onto a KBr window to form a thin film, and infrared spectra (400-2000 cm⁻¹) were acquired using a Thermo Fisher Nicolet IS5 infrared spectrometer. -1 The scan count was 32, and the resolution was 4cm. -1 The content of each microstructure was calculated. There are three types of BR microstructures: cis-1,4-structure content, trans-1,4-structure content, and 1,2-structure content, corresponding to the content at 738 cm⁻¹ in the FTIR spectrum, respectively. -1 967cm -1 and 911cm -1 The absorption peaks at that location, based on the heights of these three characteristic peaks (A) 738 A 967 and A 911 The content of each configuration can be calculated using the following formula:

[0088]

[0089] Where A = 17667A 738 +4741.4A 967 +3673.8A 911 .

[0090] The Mooney viscosity of the compound was determined according to GB / T 1232.1-2016, and the AKRON abrasion was determined according to GB / T 1689-2014.

[0091] Example 1

[0092] Under nitrogen protection, 100 mL of hexane, 4.6 mmol of neodymium octanoate, 46 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride, and 230 mmol of butadiene were added and stirred at 30 °C for 30 min. Then the temperature was raised to 60 °C, and 13.8 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added. The mixture was then aged for 2 h to obtain a catalyst in a homogeneous solution state, namely the homogeneous rare earth catalyst C1.

[0093] Under nitrogen protection, 10 mL of hexane, 0.31 mmol of nickel naphthenate (reagent grade, purchased from Inocare, hereinafter the same), and 1.89 mmol of triisobutylaluminum were mixed at 30 °C and aged at 30 °C for 30 min to obtain the first mixed component. The first mixed component was then added to a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component based on nickel naphthenate was 1:8.5 × 10⁻⁶). -5 Then, boron trifluoride diethyl ether complex (the molar ratio of butadiene to boron trifluoride diethyl ether complex is 1:3.4×10) is added. -5 The mixture was stirred thoroughly and polymerization was carried out at a polymerization temperature of 50°C. When the conversion rate reached 82%, diisobutylaluminum hydride (the molar ratio of butadiene to diisobutylaluminum hydride was 1:9×10⁻⁶) was added to the reactor. -5 The molar ratio of butadiene to catalyst C1 (calculated as neodymium octanoate) is 1:1.8×10⁻⁶. -5 The polymerization reaction was continued at 50℃ for 5 hours (polymerization conversion rate is shown in Table 2). Then, 1 ml of ethanol and 1 g of antioxidant 1076 were added to the obtained adhesive solution, stirred evenly, dried at room temperature, and then placed in a vacuum drying oven at 50℃ until constant weight was obtained to obtain polybutadiene rubber. In addition, the content of cis-1,4-polymer structure is shown in Table 2.

[0094] Example 2

[0095] Under nitrogen protection, 100 mL of hexane, 4.6 mmol of neodymium octanoate, 46 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride, and 211.6 mmol of butadiene were added and stirred at 30 °C for 30 min. Then the temperature was raised to 60 °C, and 13.8 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added. The mixture was then aged for 2 h to obtain a catalyst in a homogeneous solution state, namely the homogeneous rare earth catalyst C2.

[0096] Under nitrogen protection, 10 mL of hexane, 0.35 mmol of nickel naphthenate, and 2.1 mmol of triisobutylaluminum were mixed at 30 °C and aged at 30 °C for 30 min to obtain the first mixed component. The first mixed component was then added to a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component based on nickel naphthenate was 1:9.6 × 10⁻⁶). -5 Then, boron trifluoride diethyl ether complex (the molar ratio of butadiene to boron trifluoride diethyl ether complex is 1:3.48×10) is added. -5The mixture was stirred thoroughly and polymerization was carried out at a polymerization temperature of 50°C. When the conversion rate reached 90%, diisobutylaluminum hydride (the molar ratio of butadiene to diisobutylaluminum hydride was 1:5.4×10⁻⁶) was added to the reactor. -5 The molar ratio of catalyst C2 (butadiene to catalyst based on neodymium octanoate) is 1:9×10⁻⁶. -6 The polymerization reaction was continued at 50℃ for 5 hours (polymerization conversion rate is shown in Table 2). Then, 1 ml of ethanol and 1 g of antioxidant 1076 were added to the obtained adhesive solution, stirred evenly, dried at room temperature, and then placed in a vacuum drying oven at 50℃ until constant weight was obtained to obtain polybutadiene rubber. In addition, the content of cis-1,4-polymer structure is shown in Table 2.

[0097] Example 3

[0098] Under nitrogen protection, 100 mL of hexane, 4.1 mmol of neodymium octanoate, 49.2 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride, and 184.5 mmol of butadiene were added and stirred at 30 °C for 30 min. Then the temperature was raised to 60 °C, and 14.35 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added. The mixture was then aged for 2 h to obtain a catalyst in a homogeneous solution state, namely the homogeneous rare earth catalyst C3.

[0099] Under nitrogen protection, 10 mL of hexane, 0.30 mmol of nickel naphthenate, and 1.7 mmol of triisobutylaluminum were mixed at 30 °C and aged at 30 °C for 30 min to obtain the first mixed component. The first mixed component was then added to a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component based on nickel naphthenate was 1:8.2 × 10⁻⁶). -5 Then, boron trifluoride diethyl ether complex was added (the molar ratio of butadiene to boron trifluoride diethyl ether complex was 1:2.87×10). -5 The mixture was stirred thoroughly and polymerization was carried out at a polymerization temperature of 50°C. When the conversion rate reached 75%, diisobutylaluminum hydride (the molar ratio of butadiene to diisobutylaluminum hydride was 1:1.43×10⁻⁶) was added to the reactor. -4 The molar ratio of butadiene to catalyst C3 (calculated as neodymium octanoate) is 1:2.38×10⁻⁶. -5 The polymerization reaction was continued at 50℃ for 5 hours (polymerization conversion rate is shown in Table 2). Then, 1 ml of ethanol and 1 g of antioxidant 1076 were added to the obtained adhesive solution, stirred evenly, dried at room temperature, and then placed in a vacuum drying oven at 50℃ until constant weight was obtained to obtain polybutadiene rubber. In addition, the content of cis-1,4-polymer structure is shown in Table 2.

[0100] Example 4

[0101] Under nitrogen protection, 100 mL of hexane, 4.2 mmol of neodymium octanoate, 37.8 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride, and 201.6 mmol of butadiene were added and stirred at 30 °C for 30 min. Then the temperature was raised to 60 °C, and 14.7 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added. The mixture was then aged for 2 h to obtain a catalyst in a homogeneous solution state, namely the homogeneous rare earth catalyst C4.

[0102] Under nitrogen protection, 10 mL of hexane, 0.31 mmol of nickel naphthenate, and 1.79 mmol of triisobutylaluminum were mixed at 30 °C and aged at 30 °C for 30 min to obtain the first mixed component. The first mixed component was then added to a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component based on nickel naphthenate was 1:8.5 × 10⁻⁶). -5 Then, boron trifluoride diethyl ether complex (the molar ratio of butadiene to boron trifluoride diethyl ether complex is 1:3.03×10) is added. -5 The mixture was stirred thoroughly and polymerization was carried out at a polymerization temperature of 50°C. When the conversion rate reached 78%, diisobutylaluminum hydride (the molar ratio of butadiene to diisobutylaluminum hydride was 1:5.28×10⁻⁶) was added to the reactor. -4 The molar ratio of catalyst C4 (butadiene to catalyst based on neodymium octadecanate) was 1:1.76×10⁻⁶. -5 The polymerization reaction was continued at 50℃ for 13 hours (polymerization conversion rate is shown in Table 2). Then, 1 ml of ethanol and 1 g of antioxidant 1076 were added to the obtained adhesive solution, stirred evenly, dried at room temperature, and then placed in a vacuum drying oven at 50℃ until constant weight was obtained to obtain polybutadiene rubber. In addition, the content of cis-1,4-polymer structure is shown in Table 2.

[0103] Example 5

[0104] Under nitrogen protection, 100 mL of hexane, 4.5 mmol of neodymium octanoate, 67.5 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride, and 193.5 mmol of butadiene were added and stirred at 30 °C for 30 min. Then the temperature was raised to 60 °C, and 15.75 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added. The mixture was then aged for 2 h to obtain a catalyst in a homogeneous solution state, namely the homogeneous rare earth catalyst C5.

[0105] Under nitrogen protection, 10 mL of hexane, 0.30 mmol of nickel naphthenate, and 1.6 mmol of triisobutylaluminum were mixed at 30 °C and aged at 30 °C for 30 min to obtain the first mixed component. The first mixed component was then added to a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component based on nickel naphthenate was 1:8.7 × 10⁻⁶). -5 Then, boron trifluoride diethyl ether complex (the molar ratio of butadiene to boron trifluoride diethyl ether complex is 1:3.15×10) is added. -5 The mixture was stirred thoroughly and polymerization was carried out at a polymerization temperature of 50°C. When the conversion rate reached 80%, diisobutylaluminum hydride (the molar ratio of butadiene to diisobutylaluminum hydride was 1:1.1×10⁻⁶) was added to the reactor. -4 The molar ratio of butadiene to catalyst C5 (calculated as neodymium octanoate) is 1:2.2×10⁻⁶. -5 The polymerization reaction was continued at 50℃ for 5 hours (polymerization conversion rate is shown in Table 2). Then, 1 ml of ethanol and 1 g of antioxidant 1076 were added to the obtained adhesive solution, stirred evenly, dried at room temperature, and then placed in a vacuum drying oven at 50℃ until constant weight was obtained to obtain polybutadiene rubber. In addition, the content of cis-1,4-polymer structure is shown in Table 2.

[0106] Comparative Example 1

[0107] The method was carried out according to Example 1, except that the amount of catalyst C1 was 0, resulting in a comparative rubber.

[0108] Comparative Example 2

[0109] The method was carried out according to Example 1, except that the conversion rate was 65% when catalyst C1 was added, resulting in a comparative rubber.

[0110] Comparative Example 3

[0111] The method was carried out according to Example 1, except that the amount of hexane solution of diisobutylaluminum hydride added was 115 ml, and a comparative rubber was obtained.

[0112] Test Example 1

[0113] The rubbers (BR) obtained in Examples 1-5 and Comparative Examples 1-3 were compounded according to the formulations shown in Table 1 to obtain compounded rubbers. The Mooney viscosity and AKRON abrasion of the compounded rubbers are shown in Table 2. Furthermore, the compounding conditions are as follows:

[0114] The compound preparation adopts a two-stage mixing process. The internal mixer filling coefficient is 0.7. The first stage mixing temperature is set at 60℃, and the rotor speed is 80 r / min. First, all the rubber is added to the internal mixer and plasticized for 30 seconds. Then, carbon black, ASTM 103# oil, stearic acid, and ZnO are added. The compound is discharged when the temperature reaches 170℃ or the total time reaches 360 seconds. After resting for 4 hours, the second stage mixing temperature is set at 40℃, and the rotor speed is 60 r / min. The first stage compound is added to the internal mixer, along with sulfur S and accelerator TBBS, and mixed for 240 seconds before being discharged. The second stage compound is then sheeted three times longitudinally in a two-roll mill (X(S)K-160 type, Shanghai Shuangyi Rubber & Plastic Machinery Factory). The two-roll mill rollers are at room temperature.

[0115] Table 1

[0116] BR 100.00 Zinc oxide 3.00 stearic acid 2.00 sulfur 1.50 8# Industrial Reference Carbon Black 60.00 ASTM 103# oil 15.00 Accelerator TBBS 0.90 total 182.40

[0117] Table 2

[0118]

[0119] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing a polybutadiene adhesive, characterized in that, This method Includes the following steps, 1) After mixing component N and the first component B, the mixture is aged to obtain the first mixed component; 2) After mixing component A, second component B and first butadiene in a second mixture, the product of the second mixture is subjected to a second aging with first component C to obtain a second mixed component; 3) The second butadiene, the first mixed component, and the second component C are subjected to a first polymerization reaction. When the polymerization conversion rate is above 70%, the third component B and the second mixed component are added to carry out a second polymerization reaction. In this composition, component N is a nickel salt; component B is an alkylaluminum compound; component C is a halogenated compound; and component A is a rare earth salt. In step 2), the molar ratio of component A, the second component B, the first butadiene, and the first component C is 1:8-20:10-80:2-5. The halogenated compound is selected from at least one of alkylaluminum halohalogen, sesquihaloalkylaluminum, and boron trifluoride diethyl ether complex. The rare earth salt is a neodymium salt.

2. The method according to claim 1, wherein, In step 1), the molar ratio of component N to the first component B is 1:2-12.

3. The method according to claim 1, wherein, Based on the fact that component N in the first mixed component is 1 mmol, in step 2), the amount of component A is 0.01-1 mmol, the amount of the second component B is 0.12-20 mmol, the amount of the first butadiene is 2-60 mmol, and the amount of the first component C is 0.2-3.5 mmol.

4. The method according to claim 1, wherein, In step 2), the molar ratio of component A, the second component B, the first butadiene, and the first component C is 1:9-15:40-50:3-4.

5. The method according to any one of claims 1-4, wherein, Based on the fact that component N in the first mixed component is 1 mmol, in step 3), the amount of the second component C is 0.01-1 mmol.

6. The method according to any one of claims 1-4, wherein, In step 3), the molar ratio of the second butadiene, the first mixed component based on component N, the second component C, the third component B, and the second mixed component based on component A is 1:5×10. -5 -1.2×10 -4 1×10 -5 -4×10 -5 2×10 -5 -4×10 -4 5×10 -6 -3×10 -5 .

7. The method according to any one of claims 1-4, wherein, The alkylaluminum compound is selected from at least one of trialkylaluminum and dialkylaluminum hydride.

8. The method according to claim 7, wherein, The trialkylaluminum is represented by the formula Al(R)3, and the dialkylaluminum hydride is represented by the formula AlH(R)2, wherein each R in the formula Al(R)3 and AlH(R)2 is independently selected from C1-C6 alkyl groups.

9. The method according to claim 8, wherein, The alkylaluminum compound is at least one of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, tri-n-pentylaluminum, tri-n-hexylaluminum, triisobutylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, and diisobutylaluminum hydride.

10. The method according to any one of claims 1-4, wherein, The rare earth salt is at least one of neodymium octanoate, neodymium naphthenate, and neodymium phosphonate.

11. The method according to any one of claims 1-4, wherein, The haloalkylaluminum is derived from the formula Al(R) 1 )2X indicates that the sesquihaloalkylaluminum is made of the formula Al2(R 1 )3X3 means that, in the formula Al(R) 1 )2X and formula Al2(R 1 Each R in 3x3 1 Each of the X groups is independently selected from C1-C6 alkyl, benzyl, and allyl groups, and each X group is independently selected from halogens.

12. The method according to claim 11, wherein, The halogenated compound is at least one of diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, sesquiisobutylaluminum chloride, and boron trifluoride diethyl ether complex.

13. The method according to any one of claims 1-4, wherein, The conditions for the first mixing include a temperature of 10-40°C and a time of 10-200 min.

14. The method according to any one of claims 1-4, wherein, The conditions for the first aging process include a temperature of 10-80℃ and a time of 10-90 minutes.

15. The method according to any one of claims 1-4, wherein, The conditions for the second mixing include a temperature of 10-80°C and a time of 10-200 min.

16. The method according to any one of claims 1-4, wherein, The conditions for the second aging process include a temperature of 30-80°C and a time of 30-300 minutes.

17. The method according to any one of claims 1-4, wherein, The temperature of the first polymerization reaction is 40-90℃.

18. The method according to claim 17, wherein, The temperature of the second polymerization reaction is 40-90℃.

19. The method according to claim 18, wherein, The total reaction time for the first polymerization reaction and the second polymerization reaction is 1-36 hours.

20. The method according to any one of claims 1-4, wherein, Steps 1) through 3) are carried out independently in an inert atmosphere.

21. The method according to claim 20, wherein, The inert atmosphere is provided by at least one of nitrogen, helium and argon.

22. The method according to any one of claims 1-4, wherein, The first and second mixed components each contain a solvent independently, or the raw materials for the first polymerization reaction contain a solvent.

23. The method according to claim 22, wherein, The solvent is at least one of C5-C10 alkanes, C5-C10 cycloalkanes, and C6-C12 aromatics.

24. The method according to claim 22, wherein, The solvent is at least one selected from pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene, and cumene.

25. A method for preparing polybutadiene rubber, characterized in that, This method Includes the following steps, 1) The step of preparing polybutadiene adhesive according to any one of claims 1-24; 2) The step of preparing polybutadiene rubber from the polybutadiene solution.

Citation Information

Patent Citations

  • Rare earth catalyst for polymerization of butadiene, and preparation and application methods thereof

    CN103102437A

  • Rare earth catalyst and preparation method thereof and polyisoprene preparation method

    CN105985472A